The concealed art of the soul: theories of self and practices of truth in Indian ethics and epistemology - Ganeri, Jonardon (Oxford University Press, 2007)
Hidden in the cave : the Upaniṣadic self -- Dangerous truths : the Buddha on silence, secrecy and snakes -- A cloak of clever words : the deconstruction of deceit in the Mahābhārata -- Words that burn : why did the Buddha say what he did? -- Words that break : can an Upaniṣad state the truth? -- The imperfect reality of persons -- Self as performance